Accessory heads of the biceps brachii muscle: A systematic review and meta‐analysis. Issue 2 (12th April 2022) - Benes, Michal; Kachlik, David; Lev, David; Kunc, Vojtech
Abstract: The anatomy of the biceps brachii muscle has been a subject of interest to many researchers. In particular, the presence of one or more accessory heads has been reported to be the most common variation of the biceps brachii muscle. In fact, contemporary knowledge is quite inconsistent and lacks a definitive summary. Taking this into account, the present study aims to investigate the overall prevalence of the accessory heads and related questions, such as their broad morphological features, population variance, sexual dimorphism, side distribution or the changes in prevalence rates over time. A literature search of major scientific databases was conducted and produced 78 eligible articles, including 10, 603 upper limbs, for our study. Relevant data were extracted and consequently analysed with the use of random‐effects meta‐analysis. As a result, the accessory heads occur with an overall prevalence of 9.6% (95% CI 8–11%) and by far the most common is the presence of a single accessory head (8.4%; 95% CI 7–10%). Additional sub‐analyses revealed that accessory heads appear more frequently unilaterally and in males. Differences between the occurrence on the right or left side were not significant. Moreover, a decreasing trend in prevalence rates over time was observed, pointing towards an evolutionary adaptation. The innervation and blood supply of the accessory heads are nearly identical to that of the normal biceps brachii muscle. Although the accessory heads are usually asymptomatic, their potential presence must be kept in mind while interpreting various conditions. In addition, their direct clinical importance is speculated and is thought that they might be conductive to several pathological processes around the shoulder girdle and brachial region. While many of the morphological and morphometric aspects of the accessory heads are well documented, their functional value is still a matter for future investigations. Abstract : We calculated that accessory heads of the biceps brachii muscle occur with an overall pooled prevalence of 9.6% (95% CI 8–11%). The most common subtype is the presence of a single accessory head. Additional sub‐analyses revealed that accessory heads appear more frequently unilaterally and in males. Differences between the occurrence on the right or left side were not significant. A decreasing trend in prevalence rates over time was observed, pointing towards an evolutionary adaptation. The innervation and blood supply of the accessory heads are nearly identical to that of the normal biceps brachii muscle. Although the accessory heads are usually asymptomatic, their potential presence must be kept in mind when managing various pathological conditions.